PENGARUH BRAND EQUITY, PHYSICAL EVIDENCE, DAN RESPONSIVENESS TERHADAP MINAT BELI ULANG KONSUMEN DI TIARA DEWATA YEH AYA - I Komang Verdy Anantha Putra; Ni Wayan Eka Mitariani; I Gede Yudhi Hendrawan (VALUES, 2024)
Supermarket competition is getting tighter and tighter with the number of new supermarkets emerging. This causes old supermarkets to start losing their market. Tiara Dewata Yeh Aya Supermarket is one of the oldest supermarkets in Bali and is still operating today. This research aims to test and obtain empirical evidence of the influence of brand equity, physical evidence, and responsiveness on consumer repurchase interest at Tiara Dewata Yeh Aya. This research was conducted at Tiara Dewata Yeh Aya (PT. Adikarya Pangan Freshindo) using qualitative and quantitative data types. The population in this study is Tiara Dewata Yeh Aya consumers with more than 2 visits in 2023. The sample used was 80 people using a purposive sampling method. The analytical tools used are multiple linear analysis, classical assumption test, t test, and f test which is processed using Softawre SPSS vs 26. The results of this research show that brand equity has a positive and significant effect on consumer repurchase intention Tiara Dewata Yeh Aya, physical evidence has a positive and significant effect on consumer repurchase intention at Tiara Dewata Yeh Aya, responsiveness has a positive and significant effect on consumer repurchase intention at Tiara Dewata Yeh Aya